Minat ; Belajar ; Pendidikan ; J ANALISIS MINAT BELAJAR SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI DI MA GHOYATUL JIHAD KARAWANG: ANALISIS MINAT BELAJAR SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI DI MA GHOYATUL JIHAD KARAWANG - Yoga Rahmadi; Nana Suryana Nasution; Tedi Purbangkara (Jurnal Speed (Sport, Physical Education, Empowerment), 2022)
Abstract This study aims to find out what internal factors cause the lack of student interest in learning physical education in class XII at MA Ghoyatul Jihad Karawang and what external factors cause students' lack of interest in learning physical education in class XII at MA Ghoyatul Jihad Karawang. This type of research is descriptive qualitative research. The number of informants is 7 people. Data collection techniques used are observation, interviews and documentation. data analysis techniques using data reduction, data presentation and drawing conclusions. data validation technique using member check. The results showed that: 1) internal factors that caused a lack of student interest in learning Physical Education Health and Health Class XII MA Ghoyatul Jihad Karawang were: there were no internal factors that caused students' reluctance to take physical education lessons. 2) External factors that cause it are: the scorching sun and hot weather because it causes the body to become hot, tired and thirsty.